The Vikings voyage of the longships - Scandinature Film.; International Masters Publishers ([New York] : International Masters Publishers, 2008)
In the eighth century, fierce warriors from Scandanavia came across the seas and invaded Europe. These men from the north country built ships that had never been seen before. They raided villages, plundered, and took slaves. These northmen were also adventurers, and with their remarkable ships, some made it as far as North America.
DVD.
Keywords: Civilization, Viking; Northmen; Vikings; Nonfiction films; Documentary films; DVD-Video discs